Sensory characteristics and classification of commercial and experimental plain yogurts - Brown, Marissa (Kansas State University, 2010)
This research aimed to determine the sensory characteristics of commercially-available plain yogurts and examine how three "more sustainable" prototypes compared. Three experimental non-fat set-style yogurts were provided – one control and two samples that differed in fermentation time. These shortened fermentation times could result in energy reductions and potentially substantiate a “sustainable” marketing claim, a concept gaining traction with consumers. Twenty-six commercially-available yogurts varying in percent milk fat, milk type (organic or conventional), and processing (set-style, stirred, or strained/Greek-style) were also included. Using descriptive sensory analysis, a six-person highly-trained panel scored the intensity of 25 flavor, six texture, four mouth feel, and two mouth coating attributes on a 15-point numerical scale. Three replications were conducted, and all samples were tested at least 10 days prior to the end of their shelf-lives. The samples differed for 19 flavor and all texture, mouth feel, and mouth coating attributes. Cluster analysis indicated approximately seven flavor and five texture (texture, mouth feel, and mouth coating combined) clusters, resulting in 15 unique combinations of flavor and texture. Although no legal definitions exist for “sustainable,” the prototypes’ sensory characteristics were comparable to those of top-selling yogurts indicating potential market viability. This research also demonstrated potential growth opportunities. Despite the current diversity, several combinations of flavor and texture were not represented.
Keywords: Yogurt; Descriptive analysis; Flavor; Texture; Agriculture, Food Science and Technology (0359)